MENJADI GURU PENDIDIKAN AGAMA KATOLIK YANG BERDAYA SAING: MEMBANGUN KOMPETENSI PAEDAGOGIS DAN KEAGAMAAN - Kurnia Saputra, Yohanes Chandra (Bahasa Indonesia, 2024)
The background to this research highlights the important role of Catholic Religious Education in shaping the character and morals of the younger generation. However, Catholic Religious Education teachers are faced with big challenges in developing their competencies, both in terms of teaching ability and understanding of religion. Lack of development in these two aspects can hamper the effectiveness of the religious learning process in schools. Therefore, this research aims to identify and develop the pedagogical and religious competencies of Catholic Religious Education teachers, as well as formulate effective strategies and methods to improve the quality of Catholic religious teaching. The research method used is literature study, which aims to provide a strong theoretical foundation and practical solutions for improving the quality of Catholic religious education. In the conclusion, the importance of developing teacher competencies is highlighted, with strategies that include the development of sustainable training programs and teaching methods that involve a holistic approach to the development of both competencies simultaneously. Evaluation of competency development programs is also considered important to measure their impact in improving the quality of Catholic religious teaching.